Barriers to Primary Care Access in Rural Medically Underserved Areas - Suzanne Hewitt; Susan McNiesh; Lilo Fink (Rural Nurse Organization; Binghamton University, 2019)
Purpose: To explore patients' perceptions of factors that combine to limit or prevent access to primary care in rural medically underserved areas or populations (MUAPs ). Sample: Two focus group sessions were conducted with a sample of eight rural community members. Participants were identified as having had a minor illness or injury in the previous six months and having been unable to access their primary care provider (PCP) for care. Method: This qualitative study used data generated from comments shared by participants of the focus groups in response to a series of open-ended questions designed to promote meaningful dialogue. The sessions were audiotaped and transcribed by a professional transcription service. The transcribed data was then analyzed by the authors using qualitative content analysis methods to classify the data into themes. Findings: Analysis of data generated from the focus groups identified three dominant themes: People living in rural MUAPs have unique health care needs when compared to residents of urban or metropolitan areas; rural community members perceive an inability to access their PCP for sudden or unexpected illness or injury leading to foregone care, delayed care or seeking care in the emergency department for nonurgent problems; and the same-day, walk-in, immediate care model is meeting the needs of these patients. Conclusion: The 20% of the U.S. population living in rural areas who are being cared for by only 10% of the nation's primary care providers often lack access to safe, timely, effective, efficient, equitable, and patient-centered health care. Implementation of care models similar to the immediate care model in this study may offer rural community members prompt, competent, evidence-based treatment from a nurse practitioner in a timely manner. Keywords: rural, healthcare, access, barriers, immediate care, nurse practitioner, APRN DOI: http://dx.doi.org/10.14574/ojrnhc.v19i2.582